SMALL BRIBE LAW DOES NOT CONTRIBUTE TO REDUCING CORRUPTION - R. Sh. URAZBAEV (Высшее образование в России)
The author analyzes the initiated Article No. 291.2 of the Criminal Code of the Russian Federation with due consideration of anticorruption measures in education. The paper demonstrates week points of the new law and gives reasons for injustice of leveling such actions as receiving and giving small bribes on level of public danger. The author summarizes that this law negatively impacts on corruption state at universities.